Multicenter comparison of in vitro activities of FK-037, cefepime, ceftriaxone, ceftazidime, and cefuroxime. - Washington, J A (1993)
In a multicenter study, the MICs of FK-037 for 90% of the strains tested (MIC90s) were < or = 1 microgram/ml for members of the family Enterobacteriaceae other than Citrobacter freundii, Enterobacter spp., and Serratia marcescens. Activity against Pseudomonas aeruginosa was variable, with a MIC50 and a MIC90 of 4 and 32 micrograms/ml, respectively. Relative to cefepime, however, FK-037 was less active against ceftazidime-resistant isolates of Enterobacter cloacae. The MIC90 of FK-037 for methicillin-resistant staphylococci was > 16 micrograms/ml.